Relationship between hip and knee kinematics in athletic women during cutting maneuvers: A possible link to noncontact anterior cruciate ligament injury and prevention - Imwalle, L. E.; Myer, G. D.; Ford, K. R.; Hewett, T. E. (The Journal of Strength and Conditioning Research, 2009)
The purposes of this study were to compare lower-extremity kinematics during a 45° and 90° cutting maneuver and to examine the relationships between lower-extremity rotations during these maneuvers. The hypotheses tested were that greater internal hip and knee rotation angles would be observed during the cutting maneuver at a 90° angle (90° cut) compared with the maneuver performed at a 45° angle (45° cut) and that the increased internal hip and knee rotation would be related to increased knee abduction measures. Nineteen athletes from women's soccer teams (17.6 ± 2.1 yr, 165.6 ± 8.2 cm, 60.2 ± 5.6 kg) were instructed to jump across a line and cut at the appropriate angle (either 45° or 90° side-step cut) and in the appropriate direction. Lower-extremity kinematic measures were taken at peak force during the stance phase. Hip internal rotation and knee internal rotation (p = 0.008) were increased during the 90° cut compared with the 45° cut. Mean hip flexion (p < 0.001) was also greater in the 90° cut. The only significant predictor of knee abduction during both tasks was hip adduction (R = 0.49). The findings indicate that the mechanisms underlying increased knee abduction measures in athletic women during cutting tasks were primarily coronal plane motions at the hip. Trunk and hip focused strength neuromuscular training may improve the ability of athletic women to increase control of lower-extremity alignment. Therefore, these women may decrease dangerous knee loads that result from increased hip adduction during dynamic tasks, thus decreasing anterior cruciate ligament injury risk.